The bad beginning - Snicket, Lemony; Helquist, Brett (1999)
After the sudden death of their parents, the three Baudelaire children must depend on each other and their wits when it turns out that the distant relative who is appointed their guardian is determined to use any means necessary to get their fortune.
1010L
Accelerated Reader AR
Keywords: Orphans -- Juvenile fiction; Brothers and sisters -- Fiction; Humorous stories